1991
DOI: 10.1007/bf02090162
|View full text |Cite
|
Sign up to set email alerts
|

Vascular responsiveness in obstructed gut

Abstract: Multiorgan system failure due to hypotension and sepsis is an important cause of death in patients with bowel obstruction. We have investigated the pathophysiology of this entity in an animal model. After 5 days of bowel obstruction, blood flow in the superior mesenteric artery was measured with and without Pitressin and norepinephrine given in separate experiments. In controls, Pitressin in moderate dosages caused a substantial fall in gut blood flow, which was not seen in obstructed animals (blood flow reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This pharmacologic activity reduces hydroelectrolytic retention in the intestinal lumen, as well as gastric secretions, intestinal motility, biliary flow, splanchnic hypervascularization, and intestinal parietal edema. Furthermore, it increases the absorption of water and the production of intestinal mucous 52,53. Different studies on the effectiveness of octreotide at doses from 200–600 μg/day have shown a clear reduction in intestinal secretions, the eventual possibility of withdrawing the nasogastric tube, and a high grade of antiemetic and analgesic response with no relevant adverse effects 2,8,5458.…”
Section: Treatmentmentioning
confidence: 99%
“…This pharmacologic activity reduces hydroelectrolytic retention in the intestinal lumen, as well as gastric secretions, intestinal motility, biliary flow, splanchnic hypervascularization, and intestinal parietal edema. Furthermore, it increases the absorption of water and the production of intestinal mucous 52,53. Different studies on the effectiveness of octreotide at doses from 200–600 μg/day have shown a clear reduction in intestinal secretions, the eventual possibility of withdrawing the nasogastric tube, and a high grade of antiemetic and analgesic response with no relevant adverse effects 2,8,5458.…”
Section: Treatmentmentioning
confidence: 99%
“…High portal levels of VIP cause hypersecretion and splanchnic vasodilatation, with consequent hyperemia and edema of the intestinal wall that leads to further fluid accumulation [10]. Splanchnic vasodilation ultimately may cause systemic hypotension, leading to multiorgan failure and potentially death [11]. Sepsis also can occur as a result of bacterial translocation through the bowel wall secondary to the increased endoluminal pressure, stasis, and intestinal ischemia (Fig.…”
Section: Pathophysiologymentioning
confidence: 98%
“…3,4 Administration of octreotide, a synthetic analog of somatostatin, results in a reduction of gastric and intestinal secretions, a slowing of intestinal motility, and a reduction of splanchnic blood flow. 5 At the intracellular level, octreotide acts at the interstitial epithelium to decrease secretion of water, sodium, and chloride, and improve both ion and water absorption. 6 These effects may be attributed to the inhibition of vasoactive intestinal peptide, a gastrointestinal hormone known to have increased levels in patients with any form of bowel obstruction.…”
Section: Commentmentioning
confidence: 99%